Mobile app: iQuimia: The application that facilitates learning the periodic table through Technology - Herrera Soto, Anthonny Fabricio (2025)
At UTN, chemistry students face significant challenges in learning the elements of the periodic table, as they must memorize names, symbols, properties, atomic numbers, and classifications. Traditional teaching methods, based on repetitive memorization, prove insufficient. To address these difficulties, the iQuimia mobile application for Android devices was developed. This application, created in collaboration between the Information Technology program and chemistry teachers, uses interactive games that facilitate fun and progressive learning, tailored to the individual skills of the students. The qualitative research methodology included documentation analysis, focusing on the experiences of chemistry students. The iQuimia application offers an intuitive interface, detailed feedback, and a personalized educational experience without the need for differentiated roles. The development objectives include improving the retention and understanding of chemical knowledge, increasing student motivation, and promoting interactive and accessible learning. The implementation of iQuimia represents a significant innovation in the teaching of chemistry, enhancing dynamic and personalized learning and improving the integration of technology in education.